Plasma Riboflavin and Vitamin B-6, but Not Homocysteine, Folate, or Vitamin B-12, Are Inversely Associated with Breast Cancer Risk in the European Prospective Investigation into Cancer and Nutrition-Varese Cohort. Issue 6 (27th April 2016) - Agnoli, Claudia; Grioni, Sara; Krogh, Vittorio; Pala, Valeria; Allione, Alessandra; Matullo, Giuseppe; Di Gaetano, Cornelia; Tagliabue, Giovanna; Pedraglio, Samuele; Garrone, Giulia; Cancarini, Ilaria; Cavalleri, Adalberto; et al.
Abstract: Background: One-carbon metabolism—important for DNA stability and integrity—may play a role in breast carcinogenesis. However, epidemiologic studies addressing this issue have yielded inconsistent results. Objective: We prospectively investigated associations between breast cancer and plasma folate, riboflavin, vitamin B-6, vitamin B-12, and homocysteine in women recruited to the Varese (Italy) cohort of the EPIC (European Prospective Investigation into Cancer and Nutrition) study. Methods: We performed a nested case-control study on women aged 35–65 y at recruitment with a median body mass index of 25.3 kg/m 2 who gave blood samples in 1987–1992 and again in 1993–1998. Breast cancer cases identified by 31 December 2009 were individually matched to controls. RRs of breast cancer (and subtypes defined by hormone receptor status) with 95% CIs were estimated by unconditional logistic regression, controlling for matching factors and breast cancer risk factors. Results: After a median of 14.9 y, 276 breast cancer cases were identified and matched to 276 controls. Increasing plasma vitamin B-6 was associated with decreased risk of overall (RR: 0.78; 95% CI: 0.63, 0.96 for 1-SD increase), premenopausal (RR: 0.66; 95% CI: 0.48, 0.92 for 1-SD increase), estrogen receptor-positive (RR: 0.79; 95% CI: 0.63, 1.00 for 1-SD increase), and progesterone receptor-positive (RR: 0.72; 95% CI: 0.55, 0.95 for 1-SD increase) breast cancers. Increased plasma vitamin B-6 was also associated with decreased breast cancer risk in alcohol consumers (≥7 g/d) compared with consumption of <7 g/d or nonconsumption (RR: 0.71; 95% CI: 0.51, 0.99). High plasma riboflavin was associated with significantly lower risk in premenopausal women (RR: 0.45; 95% CI: 0.21, 0.94; highest compared with the lowest quartile, P trend = 0.021). Plasma homocysteine, folate, and vitamin B-12 were not associated with breast cancer risk. Conclusions: High plasma vitamin B-6 and riboflavin may lower breast cancer risk, especially in premenopausal women. Additional research is necessary to further explore these associations.